The Influence of Leadership Traits Toward Leadership Behavior: A Preliminary Investigation on Imams at Kubang Pasu, Kedah Darul Aman - Mahazan Abdul Mutalib @ Talib; Abdullah Haji Abdul Ghani (Universiti Sains Islam Malaysia, 2024)
This study investigates the integrated influence of leadership traits toward leadership behavior amongst imams of mosques in Kubang Pasu, Kedah Darul Aman. There were three leadership traits investigated in this research; leaders’ personality, religiosity, and motivation to lead or MTL. Moreover, imams’ educational background as well as managerial and past leadership experiences were also investigated as predictors for their leadership behaviors. A structured, Malay version-self-administered questionnaire was distributed to 30 imams in the district of Kubang Pasu, Kedah Darul Aman. In the regression analysis, the traits of imams tested explained 56.2% variance of leadership behavior. Specifically, results demonstrated leadership behavior could be potentially influenced highly by personality-extraversion and affective-identity MTL. Moreover, this research found that personality-conscientiousness also tends to influence leadership behavior. The same was also found for personality-neuroticism and social-normative MTL. However, the two predictors showed negative influence toward leadership behavior.